Association between statin use and the risks of glaucoma in Australia: a 10-year cohort study. Issue 1 (4th August 2021) - Yuan, Yixiong; Wang, Wei; Shang, Xianwen; Xiong, Ruilin; Ha, Jason; Zhang, Lei; Zhu, Zhuoting; He, Mingguang
Abstract : Synopsis: In a cohort of middle-aged and elderly Australians, we found that long-term statin use was associated with a higher risk of glaucoma onset. As to subtypes of statins, the increased risk was only found in rosuvastatin users. Purpose: To investigate the relationship between statin use and glaucoma onset in a 10-year longitudinal study. Methods: This nested case–control study was based on data from a large-scale cohort of Australians aged over 45 years old. Medication exposure was identified by claims records from the Pharmaceutical Benefits Scheme during the follow-up period (2009–2016). The onset of glaucoma was defined as the people with at least three claims of antiglaucoma medications. Controls matched by age, gender and cardiovascular diseases were selected from participants without prescription of antiglaucoma medications. A conditional logistic regression model was used to assess the association between statin use and glaucoma onset. Results: The proportion of statin users was higher in the case group (40.5%) than that in the control group (38.4%). After adjusting for baseline characteristics and longitudinal claims records, statin use was not associated with glaucoma onset (OR 1.04, 95% CI 0.97 to 1.11). However, an increased risk of glaucoma onset was observed in participants with a longer duration of statin use (>3 years vs <1 year: OR 1.12, 95% CI 1.04 to 1.21). With respect to specific types of statins, participants taking rosuvastatin were more likely to suffer from glaucoma (OR 1.11, 95%CI 1.01 to 1.22). The use of other statins was not significantly associated with glaucoma onset. Conclusions: Long-term statin use was found to be associated with a higher risk of glaucoma onset in this study. Regarding specific types of statins, the increased risk of glaucoma onset was only observed in users of rosuvastatin.